Russian Borrowings in the Volga German Dialect in Russell County, Kansas - Khramova, Maria (Slavia Centralis, 2020)
The present paper is based on a field investigation of the Volga German community in Russell County, Kansas. It provides a short overview of linguistic research, conducted on Volga German dialects in Kansas, and further analyses a list of Russian borrowings that was compiled in Russell in 1913. This contribution also addresses the disputable etymology of some words and expressions and discusses the lexical items from the list of 1913 that were retained in the dialect. Analysis of additional sources shows that some words that are traditionally treated as Russian borrowings acquired on the Volga may have been part of speakers’ lexicon prior to emigration and could have been borrowed from other Slavic languages.